Literature Review Video Animasi Berbasis Budaya - Aisyah Faradhilah Yasmin; Setya Yuwana Sudikan; Hendratno Hendratno (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Research conducted using the literature review method which examines culture-based animated videos has collected 74 scientific articles indexed and accessed on the Google Scholar platform published in 2014-2023 and determined 40 articles that match the variables in the research title. Based on the theories that have been studied in this research, culture-based animated videos are very suitable for the learning process to be effective, efficient and can achieve learning objectives. The use of culture-based animated videos in the learning process, especially in elementary schools, can increase motivation, interest in learning, learning outcomes and develop students' character to become better. Preserving local culture (Jombang) through animated videos is one way to prevent it from becoming extinct while also utilizing globalization as a means of connecting information on local cultural diversity in Indonesia.